MODEL PERLINDUNGAN SAKSI DAN KORBAN TINDAK PIDANA PEMILIHAN UMUM MASA PANDEMI COVID-19 DI INDONESIA - Nuristiningsih, Dwikari; Ramadhan, Nediyanto (MAJALAH KEADILAN, 2021)
This writing is entitled "Model of Protection of Witnesses and Victims of General Election Crime during the Covid-19 Pandemic in Indonesia". The formulation of the problem of this writing are: 1). Do witnesses and victims of criminal acts of general election during the Covid-19 Pandemic in Indonesia receive legal protection? and 2). What are the protections for witnesses and victims of criminal acts of general election during the Covid-19 Pandemic in Indonesia? This writing is normative-empirical legal writing, this writing is basically a combination of normative legal approaches with the addition of various empirical elements, also regarding the implementation of normative legal provisions (laws) which are carried out to collect and analyze secondary data, examine various kinds of legislation and legal theory, finally finding answers to the problems which are then compiled into a scientific work in the form of a journal.